Continuum cavity expansion and discrete micromechanical models for inferring macroscopic snow mechanical properties from cone penetration data. Issue 16 (19th August 2017) - Ruiz, Siul; Capelli, Achille; van Herwijnen, Alec; Schneebeli, Martin; Or, Dani
Abstract: Digital cone penetration measurements can be used to infer snow mechanical properties, for instance, to study snow avalanche formation. The standard interpretation of these measurements is based on statistically inferred micromechanical interactions between snow microstructural elements and a well‐calibrated penetrating cone. We propose an alternative continuum model to derive the modulus of elasticity and yield strength of snow based on the widely used cavity expansion model in soils. We compare results from these approaches based on laboratory cone penetration measurements in snow samples of different densities and structural sizes. Results suggest that the micromechanical model underestimates the snow elastic modulus for dense samples by 2 orders of magnitude. By comparison with the cavity expansion‐based model, some of the discrepancy is attributed to low sensitivity of the micromechanical model to the snow elastic modulus. Reasons and implications of this discrepancy are discussed, and possibilities to enhance both methodologies are proposed. Key Points: We propose the utility of a cavity‐expansion‐based penetration model for interpreting snow mechanical properties from penetration data We perform a model comparison between a continuum cavity‐expansion‐based penetration model and a discrete microstructural model We determine sources of model discrepancy and discuss pros and cons from both models as well as propose the utility of combining the models